Wrinkled Nitrogen-doped Carbon Belts - Juan L. Fajardo-Díaz (Nature Portfolio, 2018)
Abstract Graphene, carbon nanotubes, and fullerenes are nanomaterials with outstanding properties such as electrical, thermal, mechanical strength, flexibility, and high surface area. These nanomaterials are used as building blocks for the construction of novel and astonishing 3D-dimensional networks. In the present work, nitrogen-doped carbon belt (N-CB) structures containing wrinkled carbon fibres as building blocks were synthesized under unstable conditions in a chemical vapour deposition experiment. N-CB structures with 0.2–3.0 microns of wide and 350 nm thick were assembled from complex individual wrinkled carbon fibres grown on Co/Cu films. These complex structures have a tubular appearance, showing holed and wrinkled graphite layers. Sulphur and copper atoms drastically affect the catalytic role of cobalt, changing the conventional growth of carbon nanotubes. Chemical functional groups, N-doping, and carbons hybridizations involved in the winkled carbon fibres are investigated. These findings provides a novel material that can be used as an excellent oxygen-reduction reaction catalyst or nano-electronics component.